THE INDONESIAN ISLAMIC HIGHER EDUCATION RESPONSE TO COUNTER THE DEVELOPMENT OF THE RADICAL-EXTREMISM IDEOLOGY - Nur Rohman; Nur Kafid (UIN Raden Mas Said Surakarta, 2021)
This study aims to see and analyze the strategy of Islamic Higher Education in Indonesia to counter the radical extremes of religious understanding. Based on a survey conducted to get the new students’ responses and an in-depth interview to the campus policymakers, the study results show the potential growth of radical religious understanding in the student environment. The potential is at the level of religious thought or understanding. Although the percentage looks small (10-15 percent), it certainly can grow if left unchecked. In addition, what should be recognized is that students can embrace radical ideology before their entrance to the university, not because of it. In response, the university also took preventive steps through enforcing several policies, such as holding curriculum reviews, performing educator supervision and evaluation, and monitoring and evaluating student activities. However, there are still several obstacles in implementing the policy of preventing radical ideologies from growing wider at IAIN (now UIN) Surakarta, such as monitoring student activities outside the campus and imposing uniformity in implementing the policies at the Faculty and Department level.